Analisis Pilar Pertama pada Program Sanitasi Total Berbasis Masyarakat (STBM) di Wilayah Kerja Sungai Lokan Tanjung Jabung Timur - Putri, Fitria Eka; Hubaybah, Hubaybah; Fitri, Adelina; Aswin, Budi; Hidayati, Fajrina; Hidayat, Ahmad (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2023)
Implementation of the STBM program, the first pillar, namely Stop Defecation, is the main pillar in implementing the STBM plan which is a comprehensive sanitation entry point designed to break the chain of human waste pollution into drinking water, food and other raw water. Based on STBM data in Jambi Province, East Tanjung Jabung Regency is the Regency with the lowest access to toilets, namely 74.61% with 25.58% still defecating in the open. Based on STBM data for the first pillar in East Tanjung Jabung Regency, Sadu District is the sub-district with the lowest access to toilets compared to other sub-districts, there are still 47.17% of people who defecate in the open. Sadu sub-district is a sub-district that is included in the working area of the Sungai Lokan Community Health Center, East Tanjung Jabung District. The type of research used is qualitative with a descriptive observational approach. This research aims to analyze the Planning, Implementation, Recording and Reporting, which is used in the first pillar STBM program at the Sungai Lokan Tanjung Jabung Timur Community Health Center. The research was conducted in the working area of the Sungai Lokan Tanjung Jabung Timur Community Health Center in June-July 2023. There were 8 informants in the research consisting of 1 key informant and 7 supporting informants, the sampling technique used was purposive sampling, the instruments in this research were an interview guide, recording equipment and writing instruments. Data processing consists of data reduction, data presentation, and drawing conclusions and verification. The results of this research show that planning in the first pillar STBM program is still not good, implementation is also not good because it was last implemented in 2018, recording in the first pillar STBM program has also not been implemented well because there is no special report for this first pillar STBM program.